Chromosome-specific aberrations, rather than general aneuploidy, may drive mouse embryonic stem cell-derived teratoma metastasis - Joaquin Montilla-Rojo; Sanne Hillenius; Thomas F. Eleveld; Daniela C.F. Salvatori; Leendert H.J. Looijenga (Stem Cell Research & Therapy)
Abstract Introduction Pluripotent stem cells (PSC) are known to recurrently acquire genetic aberrations including chromosomal aneuploidy during long-term culture of which the consequences remain largely unknown. A recent study reported that xenografting of aneuploid mouse embryonic stem cells (mESC) gives rise to teratomas containing undifferentiated elements with metastatic capacity. This contrasts with benign teratomas composed of fully differentiated tissues from the three embryonic germ layers obtained by xenografting diploid mESCs. The highlighted study thus proposes that general aneuploidy may drive metastasis of PSC-derived teratomas, thus directly correlating it with malignant potential of PSCs. Main The aneuploid mESC lines used in the aforementioned study showed trisomies of chromosomes 6, 8, 11, 15 or combinations thereof. Interestingly, several of these trisomies, specifically in chromosomes 6, 8, and 11, constitute well-known chromosomal aberrations recurrently acquired in mESCs upon (long-term) in vitro culture. This is suggested to be driven by numerous (proto)oncogenes in these regions. Notably, recurrent chromosomal aberrations are also observed in human PSCs (hPSCs), mostly in chromosome 1, 12, 17, 20 and X, and have similarly been associated with the acquisition of a malignant phenotype in vitro, posing a risk to their potential clinical application. There is synteny between the chromosomes recurrently affected by such aberrations in mouse and human PSCs, namely mouse chromosome 6 and human chromosome 12 as well as mouse and human chromosome 1, suggesting a chromosome-specific phenomenon that may transcend the species barrier. Additionally, in the field of cancer, malignant (but not benign) human germ cell tumors (hGCTs), pathologically similar to the tumors derived from the aforementioned aneuploid mouse PSCs, are characterized by supernumerical copies of chromosome 12, highlighting the additional clinical relevance of these findings and the aneuploid mESC models for GCT research and treatment. Conclusions We suggest that chromosome-specific trisomies, rather than general aneuploidy, might drive teratoma metastasis upon mESC xenografting in vivo. We also observed indications of synteny between the recurrent chromosomal aberrations among human and mouse PSCs, suggesting potentially common intraspecies selection mechanisms. We finally reiterate the similarities observed between the PSC and GCT field related to chromosomal aberrations and malignancy, highlighting the relevance of these experimental models in both research fields.